Presentación del monográfico. Conectando la investigación sociológica con los problemas sociales y las políticas públicas: implicaciones para las sociedades del sur de Europa - Venegas, Mar; Martín-Lagos, María Dolores; Romão, Ana; Baptista, Luis (Revista Española de Sociología, 2020)
Europe is facing new and radical challenges that demand extraordinary resilience from EU members, especially southern European societies, because of their outlying position and specific social problems in comparison with their EU neighbours. The difficulties of building a united Europe in the wake of the economic, financial and political crisis have exposed divergences in EU governance. In this context, sociology is an important tool to inform public policies and to provide the general public with an understanding of current challenges. The uses of sociology have social, political and practical implications in fields that are especially significant for southern European societies, such as welfare, work and employment, education, migration, social cohesion and political participation. However, the usual tensions in the organization of scientific research are now particularly intense in terms of how the sociological knowledge utility is understood and communicated. The trend toward internationalization in current research systems forces research communities to compete in a global market of scientific production, where English is the dominant language, and to publish results for an academic audience. Simultaneously there is a pressing need to make sociological knowledge relevant and applicable to regional and localproblems.